Analisis Penerapan Konsep Demokrasi Pada Mahasiswa PPKn Universitas Riau - Reka, Sulistia Reka; Yessi Amalia; Sukraini; Cristian Adithya Turnip; Hamdi Abdullah Hasibuan (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to evaluate the use of the concept of democracy among students of the Pancasila and Citizenship Education (PPKn) study program of the University of Riau (UNRI). The understanding of democracy as a system of government that involves community participation needs to be realized and carried out by the younger generation, especially students. The method applied in this study is a literature study research method. Data was obtained from articles published on the national journal website which can be accessed through Google Scholar. Data is also obtained from books, magazines, and various other media. Qualitative descriptive data analysis was carried out to conclude the results of the use of the concept of democracy among students. The results of this study state that although Civic Studies students have a high awareness of the importance of democracy, further efforts are needed to promote the implementation of these ideas in everyday life. It is recommended to strengthen democracy education in the campus environment, such as holding activities that promote active participation and open dialogue among students